2019
DOI: 10.21926/obm.neurobiol.1903041
|View full text |Cite
|
Sign up to set email alerts
|

The End Effector of Ischemic Tolerance Present in Blood Plasma from Double Conditioned Donors Ameliorates Trimethyltin Provoked Damage in Brain

Abstract: Background: Many experiments have been done to demonstrate robust ischemic tolerance efficiency using mostly young and healthy animals. However, the translation of these results to usually elderly and sick patients moreover taking many various medicines has to date been disappointing. 3-Methyltin (TMT) poisoning and short-term transient cerebral ischemia cause similar damage, especially, to selectively vulnerable brain regions such as hippocampal CA1 and CA3. Methods: Using dual conditioning, we activated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Based on several works [ 36 , 97 ], it can be concluded that the end effector of ischemic tolerance passes through the blood–brain barrier, meaning that its application will not be limited to only one organ, and its action will be possible immediately in the whole organism. These assumptions were also confirmed by our results [ 96 , 97 ], where we clearly demonstrated the unequivocal effect of activated plasma on the survival of skeletal muscle cells as well as brain cells in the CA1 hippocampus.…”
Section: Ischemic Tolerance (Closing Remarks)—application Possibilitiessupporting
confidence: 90%
See 1 more Smart Citation
“…Based on several works [ 36 , 97 ], it can be concluded that the end effector of ischemic tolerance passes through the blood–brain barrier, meaning that its application will not be limited to only one organ, and its action will be possible immediately in the whole organism. These assumptions were also confirmed by our results [ 96 , 97 ], where we clearly demonstrated the unequivocal effect of activated plasma on the survival of skeletal muscle cells as well as brain cells in the CA1 hippocampus.…”
Section: Ischemic Tolerance (Closing Remarks)—application Possibilitiessupporting
confidence: 90%
“…Based on other works, it can be assumed that interleukins, stromal factor+-α, TNF-α, bradykinin-2, adenosine, opioids, NO, miRNA, and possibly catecholamines can be possible triggers of tolerance [ 95 ]. The assumption of humoral transfer clearly supports the transfer of ischemic tolerance with blood plasma from a 2× conditioned donor [ 96 , 97 ].…”
Section: The Mechanism Of Remote Ischemic Preconditioningmentioning
confidence: 82%